Penerapan Aplikasi Anates Dalam Menganalisis Kelayakan Butir Soal Pilihan Ganda Pada Elemen Etika Profesi Akuntansi - Rahmadhani, Anisa; Ma'ruf, Novia; Hakim, Luqman; Pratiwi, Vivi (Nirta Learning Centre, 2024)
This study aims to test the feasibility of items using the Anates V4 application which helps teachers to find out the quality of questions that have been made whether they meet the criteria for good questions to be tested with more effective and efficient time or need to be revised to become good questions. By utilizing the Anates application, it can help teachers to find out how good the questions that have been made, as well as measure the knowledge of students in mastering the material. The method used in this research is quantitative to determine the effect of using the Anates V4 application on the analysis of multiple choice questions of HOTS (High Order Thinking Skills). The data source used comes from primary data through filling out tests containing multiple choice questions of HOTS (High Order Thinking Skills) on Professional Ethics Elements in Accounting and Financial Institutions. According to the results of the research that has been carried out, it can be concluded that some of the questions used are feasible enough to be tested on students, of course by paying attention to some questions that are not good or the quality of the checker is not functioning, so revisions or improvements must be made. Suggestions for further research are to expand the sample by involving more schools through various backgrounds both social, economic, and geographical to increase the generalization of research results.